A multidisciplinary study to assess the ecology of the Cape sea urchin, Parechinus angulosus, and its emerging use as a bioindicator to monitor coastal resiliency - Redelinghuys, Suzanne (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
The resilience of marine species in the face of unpredictable climate change stands as a paramount concern for the maintenance of ecological stability. Under such fluctuating conditions, it is critical to understand how organisms mitigate these effects in physiological, genetic, and morphological terms. To that end, this thesis focused on the Cape sea urchin, Parechinus angulosus, employing a multidisciplinary approach encompassing morphology, genomics, and gut microbial diversity to assess its potential as a bioindicator species and elucidate its adaptive strategies in response to varying environmental conditions along the South African coastline. This was achieved through studying their anatomy in order to link observed variation to prevailing local environmental conditions, aided by the species' wide distribution range which allows insight into adaptations across broad geographic regions and ecological settings. The first empirical chapter, Chapter 3, focusing on eight key morphometric traits of test, Aristotle's lantern and spines, revealed distinct variation in the Cape sea urchin's morphology between the east and west coasts of South Africa, suggesting the presence of some level of local adaptation to the prevailing environmental factors found on the east and west coasts of South Africa. This points to potential bioindicator capabilities of the species, reflecting adaptive divergence amidst contrasting environmental conditions. Further analysis is however necessary in order to isolate specific physiological trends that may be associated with these morphometric differences, thereby enhancing and tightening their ecological implications. The second experimental chapter, Chapter 4, delved into the genetic structure of the Cape urchin by investigating genome-wide diversity, the presence of cryptic population structure, and spatial patterns of genomic diversity. Moderate genomic differentiation was detected among populations along the eastern and western coasts of South Africa by outlier loci that may undergo natural selection, which could indicate local adaptation to environmental conditions. This pattern hints at adaptive differentiation and cryptic genetic structures within the Cape sea urchin populations and emphasises the species' potential adaptive responses to localised (in this case regional) environmental pressures. Assigning functional significance to these genetic variations will require a comprehensive annotated reference genome, a limitation acknowledged in the current study. Chapter 5 explored the gut microbial diversity and revealed significant compositional variations between the east and west coast populations of South Africa, confirming regional and inter-regional variation. This chapter also highlighted the essential biochemical pathways critical to the survival of the host which is crucial for assessing the health of the urchin host. Together, the functional content of the gut bacteria and microbial diversity showcases its potential as a bioindicator for coastal ecosystem health. Logistical challenges and confounding factors like host physiology will need to be fully considered for its effective application. Overall, the findings of this doctoral research suggest that the Cape sea urchin displays promising characteristics as a bioindicator species due to its morphological, genetic, and gut microbial variations in response to environmental differences, providing a diverse array of means in which urchins could be used as bioindicators, from their uses to assess water quality and detect pollution, to ecosystem health monitoring and biodiversity studies in which sea urchin abundance, distribution, and presence are monitored. Further research, integrating these multidisciplinary approaches is recommended to validate and refine its bioindicator potential. Additionally, the development of a comprehensive annotated reference genome is imperative to harness the species' genetic information effectively. This study underscores the significance of integrating multiple disciplines in understanding how species respond to environmental change and their potentials contributions to monitor ecological resilience. The original multidisciplinary approach, combined with high computational outputs presents a promising framework for a comprehensive ecological monitoring in marine ecosystems.
Keywords: Intertidal ecology; Parechinus angulosus; Sea urchins -- Morphology; Sea urchins -- Climatic factors; Phylogeography; Morphometrics; Microbiomes; Marine invertebrates